Answer:
Hope the answer It'll help you:)
6(4x + 2) = 3(8x + 4)
Reorder the terms:
6(2 + 4x) = 3(8x + 4)
(2 * 6 + 4x * 6) = 3(8x + 4)
(12 + 24x) = 3(8x + 4)
Reorder the terms:
12 + 24x = 3(4 + 8x)
12 + 24x = (4 * 3 + 8x * 3)
12 + 24x = (12 + 24x)
Add '-12' to each side of the equation.
12 + -12 + 24x = 12 + -12 + 24x
Combine like terms: 12 + -12 = 0
0 + 24x = 12 + -12 + 24x
24x = 12 + -12 + 24x
Combine like terms: 12 + -12 = 0
24x = 0 + 24x
24x = 24x
Add '-24x' to each side of the equation.
24x + -24x = 24x + -24x
Combine like terms: 24x + -24x = 0
0 = 24x + -24x
Combine like terms: 24x + -24x = 0
0 = 0
Solving
0 = 0
Answer:
32.55
Step-by-step explanation:
He is wrong because as long as they have the same terms/ variables behind the number it doesn’t matter about if it is positive or negative